PEMODELAN KECERDASAN BUATAN UNTUK PENGENALAN CITRA ELEKTROKARDIOGRAFI (EKG) - Imam Tazi, M.Si (El-QUDWAH, 2006)
Research on artificial intelligence to identify its pattern is conducted more frequent as it is also needed more. In this research, sampling of artificial intelligence is made to identify the pattern of electrocardiography image to classify the image of normal and abnormal heart. Electrocardiography signal used is received through offline system. The introduction of this pattern uses “feed-forward back propagation network”. The extraction of EKG image is done through Swift Fourier Transformation (FFT) by using primary component analysis to reduce data dimension. The pattern identified in this system only classifies normal and abnormal patternKata kunci: Kecerdasan buatan, Citra, Elektrokardiografi